Perlindungan Hak Moral Pencipta dalam Eksekusi Fidusia Royalti Melalui Perspektif Filsafat Justin Hughes - Anggitariani Rayi Larasati Siswanta; Agustinus Supriyanto (Badan Strategi Kebijakan Hukum, 2026)
The growth of Indonesia’s creative economy offers new opportunities to utilize copyright, particularly royalty income, as a basis for fiduciary guarantees. However, this practice rais-es juridical challenges due to the potential infringement of creators’ moral rights, which are perpetual and non-transferable even when royalties are executed as fiduciary collateral. This study aims to analyze the protection of creators’ moral rights in the execution of royalty-based fiduciary guarantees through the philosophical perspective of Justin Hughes. The re-search adopts a normative juridical method with conceptual and statutory approaches. Hughes’ theoretical framework in The Philosophy of Intellectual Property, which combines Hegel’s personality theory and Locke’s labor theory, emphasizes that intellectual works em-body the creator’s personality and dignity, making them inseparable from their creators even though royalties, as a form of economic rights, are executed because they are encumbered by fiduciary guarantees. The findings reveal that moral rights protection during fiduciary exe-cution can be ensured through the role of Collective Management Institutions as intermedi-aries managing and distributing royalties. These institutions can safeguard moral rights by implementing controlled management by incorporating restriction clauses in fiduciary deeds, maintaining verified royalty data, applying escrow or cessie mechanisms in royalty transfers, conducting post-execution audits, and facilitating mediation in cases of moral rights viola-tions. Accordingly, the fiduciary use of royalties should not diminish the creator’s moral rights but instead achieve a balance between creditors’ legal certainty and the preservation of the creator’s honor and integrity.